Protocol for the three-dimensional analysis of rodent skeletal muscle - Smrithi Karthikeyan; Yoko Asakura; Mayank Verma; Atsushi Asakura (STAR Protocols)
Summary: Confocal imaging is a powerful tool capable of analyzing cellular spatial data within a given tissue. Here, we present a protocol for preparing optically cleared extensor digitorum longus (EDL) skeletal muscle samples suitable for confocal imaging/computational analysis. We describe steps for sample preparation (including perfusion fixation and tissue clearing of muscle samples), image acquisition, and computational analysis, with sample segmentation/3D rendering outlined. This protocol can be applied to characterize various cell types, including muscle satellite cells (muscle stem cells) and capillary endothelial cells within rodent skeletal muscle.For complete details on the use and execution of this protocol, please refer to Verma et al.,1 Verma et al.,2 Karthikeyan et al.,3 and Karthikeyan et al.4 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.